The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1590/1980-0037.2020v22e67037
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of overweight in schoolchildren and analysis of agreement between anthropometric methods

Abstract: The child population is strongly affected by obesity. Accessible and reliable strategies for the obesity diagnosis are of utmost importance.. The aim of this study was to identify childhood obesity according the WHO (World Health Organization): malnourished, healthy weight, overweight and obese. It was collected measures of height, Body Mass Index (BMI), Waist Circumference (WC) and Triceps Skinfold Thickness (TSF) of 449 children from Municipal School of Araras/SP, from 7 to 10 years old. It was performed a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
1
1
0
12
Order By: Relevance
“…It is suggested that AC can be used as a method of diagnosing overweight in six-to-seven-year-old children population, since it has shown a correlation between AC and overweight. This is in line with other studies (Dias, et al, 2013;Vieira, et al, 2018;Lima, et al, 2020) in which it was observed that children with increased adiposity in the abdominal region had a higher risk of becoming overweight. But there are still no guidelines suggesting reference values for this relationship, which makes it difficult to establish parameters.…”
Section: Discussionsupporting
confidence: 93%
“…It is suggested that AC can be used as a method of diagnosing overweight in six-to-seven-year-old children population, since it has shown a correlation between AC and overweight. This is in line with other studies (Dias, et al, 2013;Vieira, et al, 2018;Lima, et al, 2020) in which it was observed that children with increased adiposity in the abdominal region had a higher risk of becoming overweight. But there are still no guidelines suggesting reference values for this relationship, which makes it difficult to establish parameters.…”
Section: Discussionsupporting
confidence: 93%
“…Dessa maneira, evidencia-se deste modo como uma problemática na saúde pública em nível mundial. Assim sendo, no Brasil a sua prevalência evidencia os gastos públicos 26,27,28 .…”
Section: Recima21 -Revista Científica Multidisciplinar Issn 2675-6218...unclassified
“…Sobre os organizadores Atividade física 16,17,18,19,23,26,27,28,29,30,31,33,42,45,46,47,73,74,75,78,97,101,103,104,106,107 Autismo 16,18,19 Autista 12,14,15,17,19,22 Avaliação 5,6,8,10,12,14,15,16,19,22,23,24,25,33,36,41,81,92,94,101,…”
Section: Sobre Os Organizadoresmentioning
confidence: 99%